2015
DOI: 10.1371/journal.pone.0145086
|View full text |Cite
|
Sign up to set email alerts
|

The Price of a Neglected Zoonosis: Case-Control Study to Estimate Healthcare Utilization Costs of Human Brucellosis

Abstract: Human brucellosis has reemerged as a serious public health threat to the Bedouin population of southern Israel in recent years. Little is known about its economic implications derived from elevated healthcare utilization (HCU). Our objective was to estimate the HCU costs associated with human brucellosis from the insurer perspective. A case-control retrospective study was conducted among Clalit Health Services (CHS) enrollees. Brucellosis cases were defined as individuals that were diagnosed with brucellosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…They are most frequently associated with the conflicting needs of wildlife and agriculture and the risk of human disease (42). This confirmed the widespread existence and natural epidemic origin of brucellosis in countries along the Silk Road (43,44), which poses severe challenges to the prevention and surveillance of brucellosis in these countries.…”
Section: Discussionmentioning
confidence: 71%
“…They are most frequently associated with the conflicting needs of wildlife and agriculture and the risk of human disease (42). This confirmed the widespread existence and natural epidemic origin of brucellosis in countries along the Silk Road (43,44), which poses severe challenges to the prevention and surveillance of brucellosis in these countries.…”
Section: Discussionmentioning
confidence: 71%
“…Depending on the existing healthcare system where the patient lives, the responsibility for paying these costs can fall on the patient, patient’s family, insurer, hospital, taxpayers, or government. Human brucellosis is a disease that results in significantly higher healthcare costs compared to the average patient seeking medical care [ 38 ]. A study conducted in southern Israel revealed that healthcare utilization costs for brucellosis patients was USD $57 ( p < 0.05 ) greater before diagnosis and USD $947 ( p < 0.001 ) greater one year post diagnosis when compared to non-brucellosis cases that were matched by age, sex, hospital, and primary care physician [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human brucellosis is a disease that results in significantly higher healthcare costs compared to the average patient seeking medical care [ 38 ]. A study conducted in southern Israel revealed that healthcare utilization costs for brucellosis patients was USD $57 ( p < 0.05 ) greater before diagnosis and USD $947 ( p < 0.001 ) greater one year post diagnosis when compared to non-brucellosis cases that were matched by age, sex, hospital, and primary care physician [ 38 ]. The higher costs of patients post diagnosis stem from higher utilization of medications, spinal/skeletal diagnostic procedures, emergency room visits, and laboratory tests [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are especially important to public health, since B. melitensis is one of the most pathogenic and the most prevalent species of Brucella spp. for humans [88], and the disease may progress to the development of debilitating symptoms, with severe involvement of multiple organs and systems, and high cost of hospitalization due to the prolonged therapy recommended [89]. The close contact of rural workers with small ruminants, preferred hosts for B. melitensis, was identified as the main form of acquisition of the disease among these individuals (Table 1), which has been confirmed by the identification of a high genetic similarity between B. melitensis strains isolated from occupationally infected workers and from goat milk samples [38].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%